Fraud at Islamic Commercial Banks in Indonesia is Seen in Good Corporate Governance (GCG) and a Whistle-Blowing System - Siregar, Erwin Saputra; Sari, Gusmila; Arsa, Arsa (IAIN Kudus, 2022)
This article discusses the dynamics of internal irregularities in Islamic commercial banks in Indonesia. This paper uses secondary data for 2017-2020, published annually by Islamic commercial banks. The sample of this study consisted of 10 Islamic commercial banks, which were determined based on the criteria and the availability of existing data. The data analysis is in the form of panel data regression analysis with the help of eviews and excels applications. This study indicates that partially the proportion of independent commissioners has a significant positive effect on fraud, and the variable number of audit committee meetings and the whistle-blowing system has no significant adverse effect on fraud. While simultaneously, the variable of good corporate governance with indicators of the proportion of independent commissioners, the number of audit committee meetings, and the whistle-blowing system have a significant positive effect on fraud in Islamic commercial banks in Indonesia for the 2017-2020 period.